2009
DOI: 10.1080/15459620902905412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Debris Accumulation On and Filter Resistance to Airflow for Four Commercially Available Vacuum Cleaners

Abstract: Mortar removal with right-angle grinders can cause excessive exposure to respirable crystalline silica. To control this dust exposure, vacuum cleaners need to exhaust 2.3 m(3)/min (80 cubic feet per minute) from the grinder's exhaust hood. Maintaining this airflow while collecting as much as 15.9 kg (35 lb) of debris in the vacuum cleaner has been problematic. A laboratory study was conducted to evaluate how mortar debris affects vacuum cleaner airflow and filter pressure loss. Four vacuum cleaners were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Research has demonstrated that certain types of dust collectors used in the construction industry can do this effectively (Heitbrink and Santalla-Elias, 2009). This study also highlights the utility of a high-flow size-selective sampler for determining short duration task-based respirable quartz exposures in construction.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that certain types of dust collectors used in the construction industry can do this effectively (Heitbrink and Santalla-Elias, 2009). This study also highlights the utility of a high-flow size-selective sampler for determining short duration task-based respirable quartz exposures in construction.…”
Section: Discussionmentioning
confidence: 99%
“…The dust collection bags provided with sanders and vacuum cleaners may be ineffective as dust control measures and in providing adequate airflow and air cleaning. In using vacuum cleaners, air flow maintenance needs to be addressed as some vacuum cleaners lose noticeable amounts of air flow as debris accumulates in the vacuum cleaner (Heitbrink and Santalla-Elias 2009). In addition to ventilation, water can sometimes be used to suppress dust generation.…”
Section: Discussionmentioning
confidence: 99%
“…A length of 50 mm diameter hose linked the pre-separator to a vacuum cleaner (model DC Tromb 400c, Dustcontrol, Inc, Wilmington, NC) equipped with a part number 44017 prefilter and part number 44016 class-H13 2 final filter (Dustcontrol, Inc, Wilmington, NC). The use of a cyclonic pre-separator reduces the accumulation of dust and debris on the filter in the vacuum cleaner, which helps to maintain a steady airflow [Heitbrink and Santalla-Elias 2009]. The vacuum cleaner and preseparator are shown in Figure 1.…”
Section: Figure 1 -Wall Inside Training Center (Niosh Photo)mentioning
confidence: 99%